Challenging the patriarchy: radical feminist themes in 'The Yellow Wallpaper' - Nurhayati Purba; Kokardi, Ella Meidelin; Gihon Kusy Marpaung; Devi Tania Panjaitan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The main factor causing inequality for women is patriarchy. As in many old-school traditions, patriarchy remains in marriage where wives are urged to bow down to their husbands and the husband is regarded as the ultimate authority of the household. This research investigates the narrative of Charlotte Perkins Gilman's iconic short story, "The Yellow Wallpaper". Descriptive qualitative research and textual analysis approach are used to complete this research analysis. Along with the depiction of radical feminism, this research aims to subvert patriarchal ideals. This is in keeping with the narrator’s husband John, who works as a physician, forbids her to do anything instead locking her in the ancestral halls. The reason of his attitude as if this is the only way to cure the female narrator’s depressing nervous trouble. She is often considered let the silly fancies run in her mind and lost control. In the nursery room she is locked up, she found an irritating painting on the yellow wallpaper. Yet, she later discovered there is a woman imprisoned in the painting who is always creeping. The findings show that the yellow wallpaper symbolizes the female narrator’s suffering as a captivated creature and pushed by the patriarchy control.